The Analysis of Coordinate Conjunction on Book Entitled The Palestinian People by Baruch Kimmerling - Azizah, Vina Anis; Zhidqi, Elvan Adam; Salsabila, Assifa Nibras (Faculty of Education and Teachers Training, 2024)
The research aims to understand the uses and the structure of coordinate conjunction properly. The researchers focus on the coordinate conjunction in the book entitled The Palestinian People by Baruch Kimmerling. The Palestinian People book tells about the Palestinian history who struggles to get freedom from the colonialist. There are several sentences in every type of coordinate conjunction. Coordinate conjunction consists of for, and, nor, but, or, yet, so. The research uses a qualitative method to analyze the sentence that used coordinate conjunction. The researcher provided the number of sentences that used coordinate conjunction with the example in the findings and discussion.